Experimental cardiovascular and lung researchRemote ischemic preconditioning versus standard myocardial protection in cardiac surgery: ten years of clinical trials. A systematic review and meta-analysis - Marczak, Jakub; Bańkowski, Tomasz; Płonek, Tomasz; Negrusz-Kawecka, Marta; Kustrzycki, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
b>Objectives: To systematically review and assess the existing evidence for the applicability of remote ischemic preconditioning (rIPC) in cardiac surgery. Material and methods : Major biomedical databases: Medline, Cochrane, etc. were searched. All randomized controlled trials (RCTs) comparing rIPC and standard myocardial protection in patients submitted to cardiac surgery were included if they reported at least one of the outcomes of interest: myocardial injury markers, postoperative inotropic support, or length of ICU stay. Results: 991 patients were included in the analysis. rIPC was shown to reduce myocardial injury markers postoperatively by –0.63 SMD [–0.99 to –0.28] and postoperative inotropic requirement by –0.40 SMD [–0.66 to –0.16] in the adult patients submitted to cardiac surgery. There has been significant, yet correctable, heterogeneity of the primary outcome of interest, and the available RCTs were small sample studies. Conclusions : This meta-analysis provides evidence confirming that rIPC has potential benefits with regard to myocardial protection.